Persistent fifth aortic arch stenosis associated with type A interruption of the aortic arch: a report of six cases - Zheng, Lin; Cao, Yong-Li; Wu, Rong-Chang; Guo, Jian; Ma, Ning; Wang, Fang-Yun; Zhang, Xin; Peng, Yun (Chinese medical journal, 2019)
[...]for some reason, the fifth arch may persist unilaterally or bilaterally and completely or partially, producing a wide variety of appearances. Because of its embryologic location, the persistent fifth arch is an extra-pericardial vessel arising from the ascending aorta proximal to the origin of the brachiocephalic arteries, ending either in the dorsal aorta or in the pulmonary arteries via the sixth arch. (A) Two-dimensional echocardiography showed type-A IAA, the three brachiocephalic arteries clusters arising from the fourth aortic arch unconnected to the descending aorta; PFAA originating from the distal ascending aorta and ending in the proximal DAO; white arrow indicating the location of PFAA stenosis; (B) Continuous Doppler echocardiography showed the velocity of PFAA stenosis was 4.12 m/s, pressure gradient was 68 mmHg; (C and D) CTA images further confirmed the echocardiography findings. 4-Arch: The fifth aortic arch is in an unusually inferior position; it approaches the same level as the main pulmonary trunk and arterial duct, with all brachiocephalic arteries appearing as a cluster originating from a single connection (the fourth aortic arch) to the ascending aorta that is unconnected to the descending aorta. [...]correct diagnosis is possible by focusing attention on these characteristic changes.